Beyond Borders: Transnational Italy. (2nd October 2019) - Duncan, Derek; Grechi, Giulia; Gravano, Viviana
ABSTRACT: These three short articles investigate how exhibitions function as primary research outputs. They present critical reflections on the preparation and realisation of a series of exhibitions that drew on material produced by a large research team. Written from the perspectives of the professional curators and an academic researcher, the essays set out the theoretical premises of the exhibition as a medium of communication, and research tool. The exhibitions were part of the AHRC-funded large grant project 'Transnationalizing Modern Languages. Mobility, Identity and Translation in Modern Italian Cultures' (2014–17). The exhibition was first held at the British School at Rome between October 26 and November 11 2016, and then at the Italian Cultural Institute in London from December 5 2016 to January 14 2017. Further iterations have been staged at the Calandra Institute, New York, the Museo Italiano, Melbourne, and at the Italian Cultural Institute in Addis Abeba and Tunis.